Value System Formation Through Project and Research Activities Part of Science Lessons - Svetlana Semenikhina; Semenikhin, Viktor; Kukenov , Zhalgas; Balzat, Sarimbayeva; Izimova, Roza (LPPM Undiksha, 2024)
More effective methodologies are still needed to achieve a system that can inspire students' interest and motivation and guide them toward science and research. This results in a need for more robust value system formation among students in educational settings. The study's main objective was to develop and implement a value system formation technology for school children in the context of active teaching, focusing on biology education. This research is a qualitative study involving biology teachers and schoolchildren in a school's educational environment. The data collection methods used in this study were interviews, observation, and document analysis. The instrument used was an observation sheet. The data analysis methods used in this research are thematic and content analysis. The results showed that Monakhov's axiom technology effectively increased students' involvement and interest in project and research activities and assisted teachers in achieving educational goals oriented towards the holistic development of students' values. In conclusion, the findings of this study show a significant increase in the number of scientific and research works conducted by students of schools participating in competitions such as DARYN and MAN over the past three years. This research is expected to inform educational policy and curriculum development, promoting the integration of project and research activities to develop individuals with solid scientific thinking, ethical values, and a sense of responsibility towards their environment.